Effect of Cinnamon (Cinnamomum cassia) as a Lipid Lowering Agent on Hypercholesterolemic Rats - Rahman, Sonia; Begum, Halima; Rahman, Zaida; Ara, Ferdous; Iqbal, Md. Jalaluddin; Yousuf, Abul Kalam Mohammad (Journal of Enam Medical College, 2013)
Background: Dyslipidemia is one of the important causes of cardiovascular disease related mortality and morbidity. Recently it has become a significant issue in public health problem of developing countries. The purpose of the study was to find a suitable solution for reducing blood lipid in dyslipidemic patients by conducting a research on the effect of cinnamon in hypercholesterolemic rats. Objective: To study the lipid lowering effect of Cinnamomum cassia on experimentally induced hypercholesterolemic rats. Materials and Methods: This study was done on 30 male Long Evans rats weighing about 200–210 gram. For convenience, the study was divided into two experiments — Experiment I and Experiment II. In experiment I, 12 animals were divided into two groups. One was Group A (n = 6, control group) fed on laboratory diet and the other was Group B (n = 6) fed on laboratory diet and cinnamon for 35 days. In experiment II, the remaining 18 rats were fed fatty mixture diet containing 1% cholesterol and 0.25% cholic acid. The hypercholesterolemic rats were then divided into 3 groups, Group C, D, and E (n=6 in each group). Group D and Group E were additionally fed on cinnamon powder and tablet atorvastatin for 35 days respectively. Serum TC, TG, LDL-C and HDL-C were measured after 35 days. Results: Fatty mixture diet increased TG, TC and LDL-C significantly. Cinnamon treated fatty mixture diet group showed that Cinnamomum cassia decreased plasma TC, TG and LDL-C. Atorvastatin therapy decreased TC, TG and LDL-C levels significantly compared with the lowering effect of cinnamon. Conclusion: The results of this experimental study indicate that Cinnamomum cassia can act as a hypocholesterolemic agent and thereby can improve cardiovascular functions. Journal of Enam Medical College; Vol 3 No 2 July 2013; Page 94-98 DOI: http://dx.doi.org/10.3329/jemc.v3i2.16132